IDENTIFICATION OF CHILLI PLANTS PLANTING ORGANISMS IN TEKO VILLAGE, LOMBOK TIMUR - muhammad anwar; Rizal Ahmadi; Muhammad Nashrudin (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
The main objective of this research is to identify and introduce various types of pests to farmers in Teko Village, Pringgebaya District. The method used is a survey method with a data collection approach in the form of direct observation on the expanse of chili plants and questionnaires as a guide for interviews with respondent farmers. Identification of pests on chili plants in Teko Village, namely: yellow virus, anthracnose fruit rot, fruit and leaf rot, whitefly, weeds (puzzle grass, spinach, and grass weeds).